2018
DOI: 10.1002/cpt.983
|View full text |Cite
|
Sign up to set email alerts
|

Gaining Mechanistic Insight Into Coproporphyrin I as Endogenous Biomarker for OATP1B‐Mediated Drug–Drug Interactions Using Population Pharmacokinetic Modeling and Simulation

Abstract: This study evaluated coproporphyrin I (CPI) as a selective endogenous biomarker of OATP1B‐mediated drug–drug interactions (DDIs) relative to clinical probe rosuvastatin using nonlinear mixed‐effect modeling. Plasma and urine CPI data in the presence/absence of rifampicin were modeled to describe CPI synthesis, elimination clearances, and obtain rifampicin in vivo OATP Ki. The biomarker showed stable interoccasion baseline concentrations and low interindividual variability (<25%) in subjects with wildtype SLCO1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
142
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(148 citation statements)
references
References 37 publications
5
142
1
Order By: Relevance
“…Subsequently, we evaluated the predictability of the DDIs between statins and RIF in the same clinical dataset, taking into account the difference between the in vitro K i of RIF for statins and CP‐I. Accounting for intersubstrate differences in K i is consistent with the recent report of Barnett et al ., who considered the IC 50 values of RIF for both CP‐I and rosuvastatin in vitro and conducted mixed model analysis of clinical interaction data. Such considerations enhance the value of a PBPK model used to translate CP‐I interaction data to other OATP1B substrates.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Subsequently, we evaluated the predictability of the DDIs between statins and RIF in the same clinical dataset, taking into account the difference between the in vitro K i of RIF for statins and CP‐I. Accounting for intersubstrate differences in K i is consistent with the recent report of Barnett et al ., who considered the IC 50 values of RIF for both CP‐I and rosuvastatin in vitro and conducted mixed model analysis of clinical interaction data. Such considerations enhance the value of a PBPK model used to translate CP‐I interaction data to other OATP1B substrates.…”
mentioning
confidence: 69%
“…Barnett et al . estimated in vivo K i,u for the RIF‐mediated inhibition of hepatic elimination clearance using empirical models for CP‐I and rosuvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the change in renal clearance is unlikely the cause of the observed increase in plasma concentration, especially for coproporphyrin I. In addition, recent model‐based analysis suggested that renal clearance of coproporphyrin I accounts for ≈15% of total elimination . Therefore, even the complete suppression of renal elimination cannot explain the observed increase in plasma concentration.…”
Section: Discussionmentioning
confidence: 95%
“…made an assumption that nonhepatic clearance is dominated by urinary elimination. However, an earlier model‐based analysis of CPI, which was based on C‐labeled coproporphyrin dosing, suggested some involvement of nonbiliary, nonrenal elimination pathways . Overall, we currently have incomplete understanding of the elimination profiles of CPI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Barnett et al . reported model‐based analyses of CPI kinetic profiles in the presence of rifampin and demonstrated that similar in vivo K i values can be obtained from CPI and rosuvastatin kinetic profiles.…”
mentioning
confidence: 93%